EMDB Web Resources. Issue 1 (9th April 2018) - Abbott, Sanja; Iudin, Andrii; Korir, Paul K.; Somasundharam, Sriram; Patwardhan, Ardan
Abstract: The Electron Microscopy Data Bank (EMDB) is a global, openly accessible archive of biomolecular and cellular 3‐D reconstructions derived from electron microscopy (EM) data. EMBL‐EBI develops Web‐based resources to facilitate the reuse of EMDB data. Here we provide protocols for how these resources can be used for searching EMDB, visualizing EMDB structures, statistically analyzing EMDB content, and checking the validity of EMDB structures. Protocols for searching include quick link categories from the main page, links to latest entries released during the weekly cycle, filtered browsing of the entire archive, and a form‐based search. For visualization, the 'volume slicer' enables slices of EMDB entries to be visualized interactively and in three orthogonal directions. The EMstats Web service provides up‐to‐date interactive statistical charts analyzing EMDB. All EMDB entries have 'Visual Analysis' pages that provide basic validation information for the entry. © 2018 by John Wiley & Sons, Inc.